Atheroprotective immunity and cardiovascular disease: therapeutic opportunities and challenges. (November 2015) - Nilsson, J.; Lichtman, A.; Tedgui, A.
Abstract: Emerging knowledge of the role of atheroprotective immune responses in modulating inflammation and tissue repair in atherosclerotic lesions has provided promising opportunities to develop novel therapies directly targeting the disease process in the artery wall. Regulatory T (Treg) cells have a protective role through release of anti‐inflammatory cytokines and suppression of autoreactive effector T cells. Studies in experimental animals have shown that blocking the generation or action of Treg cells is associated with more aggressive development of atherosclerosis. Conversely, cell transfer and other approaches to expand Treg cell populations in vivo result in reduced atherosclerosis. There have been relatively few clinical studies of Treg cells and cardiovascular disease, but the available evidence also supports a protective function. These observations have raised hope that it may be possible to develop therapies that act by enforcing the suppressive activities of Treg cells in atherosclerotic lesions. One approach to achieve this goal has been through development of vaccines that stimulate immunological tolerance for plaque antigens. Several pilot vaccines based on LDL‐derived antigens have demonstrated promising results in preclinical testing. If such therapies can be shown to be effective also in clinical trials, this could have an important impact on cardiovascular prevention and treatment. Here, we review the current knowledge of the mode of action of atheroprotective immunity and of the ways to stimulate such pathways in experimental settings. The challenges in translating this knowledge into the clinical setting are also discussed within the perspective of the experience of introducing immune‐based therapies for other chronic noninfectious diseases.